Induction of cytochromes P450 in small intestine by chemopreventive compounds - Krizkova, Jitka; Burdova, Kamila; Hudecek, Jiri; Stiborova, Marie; Hodek, Petr (Neuro endocrinology letters, 2008)
OBJECTIVES: Since flavonoids and other natural compounds exert beneficial effects on human health, their consumption rapidly increases. However, they can modulate the activity of xenobiotic-metabolizing enzymes involved in activation and detoxification of food and environmental carcinogens. Thus, their potential negative effects should be examined. METHODS: The induction effects of selected chemopreventive compounds, administered per orally by gastric gavages to rats, on cytochrome P450 (CYP) 1A and 2B were determined in liver and small intestine using Western blotting analysis and specific metabolic activity assays. RESULTS: Comparing CYPs expression along small intestine, the highest induction was observed in the proximal part near pylorus with rapid decrease towards the distal part. In response to chemopreventive compounds, the marked induction of CYP1A and CYP2B in liver was observed after diallyl sulphide and flavone treatment. In small intestine, beta-naphthoflavone, diallyl sulphide and curcumin induced CYP1A1 and CYP2B1. In both tissues, resveratrol did not significantly affect CYPs expression. The results of Western blotting detection of CYPs correlate well with their specific enzymatic activities. CONCLUSIONS: Presented data indicate ambiguous impact of chemopreventive compounds on cytochromes P450, main xenobiotic-metabolizing enzymes. Thus, the question of safety and unlimited consumption of these compounds arises.
Keywords: Liver; xenobiotika; flavonoidy; Animals; Anticarcinogenic Agents; Sulfides; Rats; sulfidy; Rats, Wistar; játra; Blotting, Western; Curcumin; tenké střevo; Allyl Compounds; Resveratrol; Flavonoids; Intestine, Small; kurkumin; stilbeny; Stilbenes; Cytochrome P-450 CYP1A1; antikarcinogenní látky; resveratrol; western blotting; Cytochrome P-450 CYP2B1; Male; Xenobiotics; systém (enzymů) cytochromů P-450; cytochrom P-450 CYP1A1; beta-naftoflavon; krysa rodu Rattus; zvířata; mužské pohlaví; beta-Naphthoflavone; cytochrom P-450 CYP2B1; Cytochrome P-450 Enzyme System; alylové sloučeniny; potkani Wistar